General Geology and Petrography of Volcanic Rocks in Kampung Keroh, Kuala Krai, Kelantan. - Noor Naimah Muhammad (2015)
The study area is located at Kampung Keroh, Kuala Krai which is near to Tanah Merah, Machang and Jeli area. The coordinate for this study area are from (1\105°391 0.0", E102°10'56.67") to (N05°39'10.0", El 02°13'57.0") and (N05°36'36.0", El 02°10'56.67") to (N05°36'36.0", El02°13'57.0"). The study area was covered exactly 25 km2. The purpose of the study is to produce the geological map of the study area, to determine the type of volcanic rock in the study area and to determine the volcanic rock based on texture. Geology research included lithology, structure, texture, geomorphology, stratigraphy and petrography at Kampung Keroh, Kuala Krai. Lithologies found in an area are andesite, pyroclastic and interbedded shale, sandstone and siltstone. From field works analysis, characteristic found was clearly show the radial, parallel and dendritic drainage system. Thin section and hand specimen was the only method that used in this study for determine the type of volcanic rock. According to texture and hand specimen, the type of volcanic rock that found in study area was an andesite. The color was an intermediate which is light grey.